Sustainable innovation : build your company's capacity to change the world - Hargadon, Andrew (Innovation and technology in the world economy., 2015)
If we can carry in our pockets more computing power than the Apollo program needed to put a man on the moon, why can't we solve problems like climate change, famine, or poverty? The answer lies, in part, in the distinctive challenges of creating innovations that address today's pressing environmental and social problems. In this groundbreaking book, Andrew Hargadon shows why sustainable innovation--the development of financially viable products that support a healthy environment and communities--is so difficult when compared to creating the next internet ventures or mobile apps that disregard these criteria. While other books treat innovation across sectors equally, Hargadon argues that most effective innovation strategies hinge on attention to the context in which they are pursued. Instead of relying on a stale set of "best practices," executives must craft their own strategies based on the particulars of their industries and markets. But, there are some rules of the road that foster a triple bottom line; this book provides a research-based framework that outlines the critical capabilities necessary to drive sustainable innovation: a long-term commitment, nexus work, science and policy expertise, recombinant innovation, and robust design. Sustainable Innovation draws on a wide range of historical and contemporary examples to show business readers and their companies how to stand on the shoulders of successful pioneers